The global landscape of drug development for kidney cancer. (September 2020) - Trapani, D.; Curigliano, G.; Alexandru, Eniu; Sternberg, C.N.
Highlights: Drug development for the treatment of patients with kidney cancer (RCC) is mainly concentrated in high- income countries. The Regional distribution of clinical trials for RCC is not aligned with the burden of RCC. The polarization of drug development in few countries can widen the ample gaps in the knowledge of benefit of pharmacological agents in different populations. Generalizability of clinical findings from trials may not be generalizable to non-Caucasian populations, when inclusiveness of diverse ethnic groups is poor. The implementation of clinical trials can be instrumental to improve the knowledge in poorly- included populations, thus being strategic to benefit patients broadly. Abstract: Renal cell cancer (RCC) is the third most diagnosed genitourinary malignancy in the world. Nearly a half of the diagnoses and 60% of related deaths occur in low-middle income countries (LMs), where prognosis is generally poor. We conducted a systematic research of ClinicalTrials.gov, searching RCC ongoing studies for adult patients. We included 205 trials in the final analysis. The enrolling centers were mainly distributed in high-income settings (88.9%). We estimated 94.6% of the trial population was enrolled in only five countries and none in LMs. Clinical drug development for RCC is driven by early phase studies, mainly assessing small molecule tyrosine kinase inhibitors and immunotherapy or the combination. Sixty percent of the trials were industry sponsored. Only a minority of the trials were in the early setting of care, adjuvant or neoadjuvant therapy. Disparities in drug development in LMs mirror a common underestimation of the value of research among the national priorities in cancer health planning, resulting in poor ethnic diversity and inclusiveness. This commonly results in incomplete knowledge of activity and safety of medicines across different ethnic groups, with consequences on priorities for cancer interventions and estimates of benefit in LMs patients. The use of RCC as a case study for inclusiveness suggests poor inclusion of non– Caucasian populations in the trials, especially trials testing new immunotherapy and targeted agents where RCC drug development is more pronounced, resulting in issues of generalizability in other ethnic groups when these compounds are approved with no ethnic restrictions or specifications.